1984
DOI: 10.2478/cttr-2013-0537
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Tobacco Leaf Quality: an Investigation of the Literature

Abstract: This paper comprises a review of the published literature (1936-1979) dealing with the relationship between the chemical constituents of tobacco and smoke and tobacco and smoke quality. Various components thought to be influential in determining quality are identified; conclusions of researchers regarding the effects of these components are recorded and discussed. A summary table is presented which details the nature of the relationship between these constituents and tobacco quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…The slightly acidic pH and the mesophilic temperature (RT) promote growth of these groups of microorganisms which are supposed to rapidly metabolize reducing sugars and available malic and citric acids. Organic acids are important constituents of tobacco because they directly influence the pH during fermentation and, consequently, smoke aroma and taste (34). The pH shift from acidic to alkaline values is a hallmark of Toscano cigar tobacco fermentation; it defines the final cigar basic characteristics and distinguishes cigars from cigarettes which are made with acidic nonfermented tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slightly acidic pH and the mesophilic temperature (RT) promote growth of these groups of microorganisms which are supposed to rapidly metabolize reducing sugars and available malic and citric acids. Organic acids are important constituents of tobacco because they directly influence the pH during fermentation and, consequently, smoke aroma and taste (34). The pH shift from acidic to alkaline values is a hallmark of Toscano cigar tobacco fermentation; it defines the final cigar basic characteristics and distinguishes cigars from cigarettes which are made with acidic nonfermented tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Undesirable fermentation by-products, such as tobacco-specific nitrosamines (TSNA) (5,20), whose increase in concentration parallels that of nitrite, are generated during fermentation. An additional unpleasant by-product of organic acid metabolism is oxalic acid, which negatively influences the tobacco taste (34). Minimizing the generation of nitrite and TSNA represents a major goal of tobacco fermentation technology.…”
mentioning
confidence: 99%
“…The amount of this diterpene was higher in the cutter grades than either the leaf or lug grades (Tables 3 and 5 Several studies have identified a positive association between phenolic content and quality (Mendel et al 1984;Kallianos 1976). …”
mentioning
confidence: 94%
“…Nicotine, protein and carbohydrate, the main chemical components of tobacco leaves, have played an important role in the formation of tobacco quality. Generally, tobacco with balanced nitrogen, nicotine and carbohydrate contents tastes better than that with lower or higher contents (Mendell et al 1984). Although many studies have been reported on different adverse effects of Cd, none has focused on the association between Cd stress and tobacco quality.…”
mentioning
confidence: 99%